2021
DOI: 10.1093/jxb/erab416
|View full text |Cite
|
Sign up to set email alerts
|

The temperature-regulated DEAD-box RNA helicase CrhR interactome: autoregulation and photosynthesis-related transcripts

Abstract: RNA helicases play crucial functions in RNA biology. In plants, RNA helicases are encoded by large gene families, performing roles in abiotic stress responses, development, the post-transcriptional regulation of gene expression as well as house-keeping functions. Several of these RNA helicases are targeted to the organelles, mitochondria and chloroplasts. Cyanobacteria are the direct evolutionary ancestors of plant chloroplasts. The cyanobacterium Synechocystis 6803 encodes a single DEAD-box RNA helicase, CrhR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 102 publications
1
13
0
Order By: Relevance
“…Overall, CrhR appears to play a role in maintaining homeostasis of photosynthesis in response to conditions resulting in over-reduction of the ETC. This crucial conclusion is supported by the results presented here combined with previous physiological and omics analysis, which suggest that CrhR regulates translation of protein products required to adapt to environmental conditions that perturb ETC homeostasis [ 11 , 25 , 27 , 35 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overall, CrhR appears to play a role in maintaining homeostasis of photosynthesis in response to conditions resulting in over-reduction of the ETC. This crucial conclusion is supported by the results presented here combined with previous physiological and omics analysis, which suggest that CrhR regulates translation of protein products required to adapt to environmental conditions that perturb ETC homeostasis [ 11 , 25 , 27 , 35 ].…”
Section: Discussionsupporting
confidence: 84%
“…These results support the conclusion that a phytochrome-mediated mechanism regulates the post-transcriptional accumulation of CrhR protein via an auto-regulatory process ( Figure 9 b). This conclusion was supported by the observation that the crhR transcript is a major target for CrhR binding [ 35 ]. Together, the data suggest that a potentially conserved phytochrome-mediated mechanism imparts translational control in response to light signals in cyanobacteria, with CrhR performing an active role in the process.…”
Section: Discussionmentioning
confidence: 72%
“…CuSO 4 (2 mM) was used to induce the expression of the Cu 2+ -responsive petE promoter, 51 while the petJ promoter was induced by removing Cu 2+ from the medium through centrifugation and resuspension. For high-density cultivation used for ATP synthase purification, Synechocystis 6803 overexpressing P petE -atpB-3xFLAG was cultured in the cell-DEG system as reported previously 52 using freshwater medium 53 with the following modifications: Na 2 EDTA and CuSO 4 were not included in the medium, and 10 mg/mL kanamycin or 5 mg/mL gentamicin was added.…”
Section: Lead Contactmentioning
confidence: 99%
“…CrhR , the unique DEAD-box RNA helicase present in the genome of the cyanobacterium Synechocystis sp. PCC 6803, participates in redox regulation of gene expression (Kujat and Owttrim, 2000), low temperature acclimation of photosynthesis (Rosana et al, 2012; Sireesha et al, 2012), and was recently shown to interact with transcripts associated with photosynthesis (Migur et al, 2021). In plant chloroplasts, DEAD-box RNA helicases participate in ribosome biogenesis (Asakura et al, 2012; Chi et al, 2012), chloroplast differentiation (Wang et al, 2000), and responses to diverse abiotic stresses (Nawaz and Kang, 2017), but a role of these enzymes in the light-response of eukaryotic photosynthesis has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%